Outcomes of Mechanical Thrombectomy in the Early (<6-hour) and Extended (≥6-hour) Time Window Based Solely on Noncontrast CT and CT Angiography: A Propensity Score–Matched Cohort Study - Hendrix, P.; Chaudhary, D.; Avula, V.; Abedi, V.; Zand, R.; Noto, A.; Melamed, I.; Goren, O.; Schirmer, C.M.; Griessenauer, C.J. (American Journal of Neuroradiology, 2021)
BACKGROUND AND PURPOSE: Current stroke care recommendations for patient selection for mechanical thrombectomy in the extended time window demand advanced imaging to determine the stroke core volume and hypoperfusion mismatch, which may not be available at every center. We aimed to determine outcomes in patients selected for mechanical thrombectomy solely on the basis of noncontrast CT and CTA in the early (<6-hour) and extended (≥6-hour) time windows.MATERIALS AND METHODS: Consecutive mechanical thrombectomies performed for acute large-vessel occlusion ischemic (ICA, M1, M2) stroke between February 2016 and August 2020 were retrospectively reviewed. Eligibility was based solely on demographics and noncontrast CT (ASPECTS) and CTA, due to the limited availability of perfusion imaging during the study period. Propensity score matching was performed to compare outcomes between time windows.RESULTS: Of 417 mechanical thrombectomies performed, 337 met the inclusion criteria, resulting in 205 (60.8%) and 132 (39.2%) patients in the 0- to 6- and 6- to 24-hour time windows, respectively. The ASPECTS was higher in the early time window (9; interquartile range = 8–10) than the extended time window (9; interquartile range = 7–10; P = .005). Propensity score matching yielded 112 well-matched pairs. Equal rates of TICI 2b/3 revascularization and symptomatic intracranial hemorrhage were observed. A favorable functional outcome (mRS 0–2) at 90 days was numerically more frequent in the early window (45.5% versus 33.9%, P = .091). Mortality was numerically more frequent in the early window (25.9% versus 17.0%, P = .096).CONCLUSIONS: Patients selected for mechanical thrombectomy in the extended time window solely on the basis of noncontrast CT and CTA still achieved decent rates of favorable 90-day functional outcomes, not statistically different from patients in the early time window.IQRinterquartile range